FACTORS ASSOCIATED WITH DIARRHEA AMONG CHILDREN 0-59 MONTHS IN KYAKA II REFUGEE SETTLEMENT, KYEGEGWA DISTRICT- WESTERN UGANDA. A NON-INTERVENTION CROSS- SECTIONAL DESCRIPTIVE STUDY DESIGN. - Kugonza , Sarah; Turumanya, Judah; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2023)
Background: The purpose of the research was to establish dietary knowledge and the factors associated with diarrhea among children 0-59 months in Kyaka Refugee Settlement, Kyegegwa District- Western Uganda. Methodology: A quantitative methodology was embraced with 125 participants selected as a sample to represent the population in the research. Using SPSS as the data analysis tool, the researcher produced outcomes including regression and correlation that affirmed an association between the two independent variables and the dependent variable. The outcomes affirmed that hygiene practices among caretakers of children 0-59 months were one of the strongest keys that contributes to diarrhea. Results: In the results of the study, Pearson’s correlation showed a positive association between food hygiene practices and the incidence of diarrhea among children 0-59 months. Hygiene practices contributed to 91.4% (2-tailed test) cause of diarrhea among children 0-59 months. According to the study, Poor hygiene practices (71.7%), and poor disposal of feces (63.7%), were associated with diarrhea among children 0-59 months. The study also revealed that the majority of the caregivers who did not have latrines had a high risk of diarrhea infection in their children and the majority of the diarrhea cases reported were acute watery diarrhea (40%) and 15% were suspected bloody diarrhea. Conclusion: In conclusion, the prevalence of diarrhea among children 0-59 months was 7.5%, a value lower than previous statistics with evidence of a significant decline in diarrhea-related hospitalizations and death. Recommendation: Improve hand sanitation, particularly after visiting the latrine by increasing the use of hand washing stations equipped with soap and clean water among other recommendations.